2005
DOI: 10.1128/jb.187.1.77-84.2005
|View full text |Cite
|
Sign up to set email alerts
|

ThepbgPEoperon inPhotorhabdus luminescensIs Required for Pathogenicity and Symbiosis

Abstract: Photorhabdus is a genus of gram-negative Enterobacteriaceae that is pathogenic to insect larvae while also maintaining a mutualistic relationship with nematodes from the family Heterorhabditis, where the bacteria occupy the gut of the infective juvenile (IJ) stage of the nematode. In this study we describe the identification and characterization of a mutation in the pbgE1 gene of Photorhabdus luminescens TT01, predicted to be the fifth gene in the pbgPE operon. We show that this mutant, BMM305, is strongly att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 45 publications
(59 reference statements)
4
71
0
Order By: Relevance
“…This two-component system controls expression of the pbgPE operon in Photorhabdus luminescens and is associated with virulence against insects; pbgPE mutants are lacking an O-antigen, resulting in increased sensitivity to insect-produced antimicrobial peptides and acidic pH (Derzelle et al 2004;Bennett and Clarke 2005).…”
Section: Type III Secretion System ( T3ss) and Effectorsmentioning
confidence: 99%
“…This two-component system controls expression of the pbgPE operon in Photorhabdus luminescens and is associated with virulence against insects; pbgPE mutants are lacking an O-antigen, resulting in increased sensitivity to insect-produced antimicrobial peptides and acidic pH (Derzelle et al 2004;Bennett and Clarke 2005).…”
Section: Type III Secretion System ( T3ss) and Effectorsmentioning
confidence: 99%
“…We used PMB as a representative of this class of molecule for evaluating the resistance levels of different strains of Y. pestis to CAMP. While the actual relatedness of PMB to insect CAMPs is not entirely clear, it has been shown that representatives of both pathogenic and symbiotic bacteria isolated from insects are resistant to PMB (11,23,29), suggesting PMB has a spectrum of activity similar to that of insect CAMPs. Secondly, though insect CAMPs are rather heterogeneous in their structures and mechanisms of action, some insect immune peptides, such as the cecropins, have a spectrum of antibacterial activity similar to that of PMB (14).…”
Section: Vol 73 2005 Y Pestis Susceptibilities To Serum and Polymymentioning
confidence: 99%
“…A recently described species, Photorhabdus asymbiotica, was never found to be associated with nematodes but was isolated from human infections (3,12,15,22). Although a few studies have identified several Photorhabdus genes that are required for normal growth and development of the nematode (5,6,9,19,29), we have little molecular and functional data about the first step of nematode colonization and nematode specificity.…”
mentioning
confidence: 99%